The art institution of tomorrow reinventing the model - Üstek, Fatoş 1980- (Lund Humphries, 2024)
The Art Institution of Tomorrow is a unique manifesto for raising the standard of institutional practices across the world. It suggests that existing art institutions are not equipped to deal with the radical social, economic and environmental change we are living through and engage with advancement in the arts, and that unless they re-focus on their core purpose and fundamentally transform their organisational structure and operational models, they will start to lose their relevance and influence. Built on an extensive study of non-profit visual-arts organisations and the creative industries at large, and incorporating interviews with institutional leaders from throughout the sector, the book expresses a clear outline of change that art institutions will need to undergo in order to maintain their relevance for generations to come.
Keywords: Kunstbetrieb; Einrichtung; Museum